Evaluasi penerimaan pajak kendaraan bermotor (PKB) dan bea balik nama kendaraan bermotor (BBN-KB) serta dampaknya terhadap pendapatan asli daerah di Provinsi Jambi - Asri Aditya, R. Ilham; Zulfanetti, Zulfanetti; Heriberta, Heriberta (Jurnal Paradigma Ekonomika, 2021)
The purpose of this study was to analyze the factors supporting and inhibiting the achievement of revenue targets, the effectiveness of motor vehicle tax receipts and motor vehicle name transfer fees, and their relationship with the original income of Jambi Province. This study used a quantitative descriptive method, where the data obtained were analyzed using qualitative analysis techniques and quantitative analysis. The results of the qualitative analysis show that the determination of the target of motor vehicle tax revenue and motor vehicle name transfer fee in Jambi Province is still done manually based on the latest achievement/realization data plus the percentage that is expected to be achieved following the existing upward trend. from previous years. The results of the quantitative analysis show that the motor vehicle tax revenue and the transfer of motor vehicle name transfer duties in 2014-2018 in Jambi Province have not been effective following the potential for motor vehicle tax revenue and motor vehicle name transfer fee. Besides, there is also no significant relationship between the effectiveness of motor vehicle tax receipts and the effectiveness of the transfer of motor vehicle name transfer fees on the Regional Original Revenue of Jambi Province during 2014-2018, either partially or simultaneously. Â